2018
DOI: 10.3389/fimmu.2018.00447
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of the Phosphorylated Form of S100A9 from Neutrophils Is Essential for the Proinflammatory Functions of Extracellular S100A8/A9

Abstract: S100A8 and S100A9 are members of the S100 family of cytoplasmic EF-hand Ca2+-binding proteins and are abundantly expressed in the cytosol of neutrophils. In addition to their intracellular roles, S100A8/A9 can be secreted in the extracellular environment and are considered as alarmins able to amplify the inflammatory response. The intracellular activity of S100A8/A9 was shown to be regulated by S100A9 phosphorylation, but the importance of this phosphorylation on the extracellular activity of S100A8/A9 has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…8b). S100A8 and S100A9 have proinflammatory functions, and have been shown to induce CCL2 expression [4448]. We found that S100a8 and S100a9 mRNA levels were significantly increased in Adgrf5 −/− lungs at 18.5 dpc (1.6- and 1.7-fold, respectively, p < 0.001), as well as thereafter (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…8b). S100A8 and S100A9 have proinflammatory functions, and have been shown to induce CCL2 expression [4448]. We found that S100a8 and S100a9 mRNA levels were significantly increased in Adgrf5 −/− lungs at 18.5 dpc (1.6- and 1.7-fold, respectively, p < 0.001), as well as thereafter (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The increase of S100A9 protein correlates with the peak of neutrophil infiltration in the stroma that takes place at 12 to 18 hours post-wounding, 8 suggesting that the detected corneal S100A9 could be of neutrophil origin. 28 A careful investigation of the spatiotemporal expression of S100A9 following corneal abrasion will be necessary to estimate the contribution of the epithelial versus neutrophil origins of S100A9 in the cornea. The increase of S100A9 protein in the cornea between 6 and 24 hours post-wounding establishes that this protein can be a target for treatments with CAP37-derived peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated expression of S100A8 and S100A9 in the cornea has been correlated with inflammation, infection, and neovascularization. 19,28 For example, the expression levels of S100A8 and S100A9 are greatly induced in Gram-positive and Gram-negative induced bacterial keratitis. 34,35 Further, the knockdown of S100A8/S100A9 was found to decrease corneal inflammation and corneal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation of factors that modulate the cytoplasmic EF-hand Ca 2+ -binding protein S100A9-mediated signaling pathway may reveal more insights into the mechanisms responsible for enhancement of neutrophil antimicrobial activity. S100A9 could be regulated by phosphorylation, but the importance of this phosphorylation on the NET activity of this protein has not yet been extensively studied (Schenten et al, 2018). Along these lines, it is interesting to determine if the enhancement of NET release and bactericidal activity is phosphorylation-dependent.…”
Section: Discussionmentioning
confidence: 99%